BEHAVIOR OF TIMOR DEER (Cervus Timorensis) ON TYPES OF FEED IN DEER CAPTURE LAMPUNG UNIVERSITY - Imam Adhi Wijaya; Bainah Sari Dewi; Sugeng P. Harianto (Journal of People, Forest and Environment, 2023)
One of the important components in managing wildlife in captivity is the availability of forage plants (Setiawan, 2018). The main diet of deer is leaves and grasses, so these animals can consume almost all types of leaves and grass, are resistant to water shortages so that they are able to adapt to agro-ecosystem conditions. The purpose of the study was to determine the types of drop-in feed for Timor deer in the deer captivity at the University of Lampung. Data collection is done with primary data and secondary data. Data regarding the analysis of the deer's feed preference level was obtained from direct observation (Zaistev, 2015) using the palatability and description methods. With this method, recording, weighing the type of feed provided by the manager and analysis of the adequacy of deer feed in captivity is carried out. Observations were carried out for 14 days with time intervals starting from 06.00-18.00 WIB. Perceptions were pursued for 14 days with rest span beginning from 06.00-18.00 WIB. In view of the seven sorts of drop-in feed above, elephant grass (Pennisetum purpureum) is a kind of food that is extremely well known with deer with a genuinely enormous level of inclination, which is 56.14%, then, at that point, trailed by grass rayutan 12.40%, sauhen grass with a level of 9 .14%, lamtoro with a level of 8.57%, teki grass 5.83%, reeds 4.68%, and sembung sambat 3.77%. The food that was first chosen and eaten by the deer was elephant grass (Pennisetum purpureum) and proceeded with sauhen grass (Penicum colonum). Higher elephant grass (Pennisetum purpureum).